Tissue-Specific Orchestration of Gilthead Sea Bream Resilience to Hypoxia and High Stocking Density - Martos-Sitcha, Juan Antonio; Simó-Mirabet, Paula; de las Heras, Verónica; Calduch-Giner, Josep Àlvar; Pérez-Sánchez, Jaume (Frontiers in Physiology, 2019)
Two different O2 levels (normoxia: 75-85% O2 saturation; moderate hypoxia: 42-43% O2 saturation) and stocking densities (LD: 9.5, and HD: 19 kg/m3) were assessed on gilthead sea bream (Sparus aurata) in a 3-week feeding trial. Reduced O2 availability had a negative impact on feed intake and growth rates, which was exacerbated by HD despite of the improvement in feed efficiency. Blood physiological hallmarks disclosed the enhancement in O2-carrying capacity in fish maintained under moderate hypoxia. This feature was related to a hypo-metabolic state to cope with a chronic and widespread environmental O2 reduction, which was accompanied by a differential regulation of circulating cortisol and growth hormone levels. Customized PCR-arrays were used for the simultaneous gene expression profiling of 34-44 selected stress and metabolic markers in liver, white skeletal muscle, heart and blood cells. The number of differentially expressed genes ranged between 22-19 in liver, heart and white skeletal muscle to 5 in total blood cells. Partial Least-Squares Discriminant Analysis (PLS-DA) explained (R2Y(cum)) and predicted (Q2Y(cum)) up to 95% and 65% of total variance, respectively. The first component (R2Y=0.2889) gathered fish on the basis of O2 availability, and liver and cardiac genes on the category of energy sensing and oxidative metabolism (cs, hif-1α, pgc1α, pgc1β, sirts 1-2-4-5-6-7), antioxidant defence and tissue repair (prdx5, sod2, mortalin, gpx4, gr, grp-170, prdx3) and oxidative phosphorylation (nd2, nd5, coxi) highly contributed to this separation. The second component (R2Y=0.2927) differentiated normoxic fish at different stocking densities, and the white muscle clearly promoted this separation by a high over-representation of genes related to GH/IGF system (ghr-i, igfbp6b, igfbp5b, insr, igfbp3, igf i). The third component (R2Y=0.2542) discriminated the effect of stocking density in fish exposed to moderate hypoxia by means of hepatic fatty acid desaturases (fads2, scd1a, scd1b) and muscle markers of fatty acid oxidation (cpt1a). All these findings disclose the different contribution of analysed tissues (liver ≥ heart > muscle > blood) and specific genes to the hypoxic- and crowding stress-mediated responses. This study will contribute to better explain and understand the different stress resilience of farmed fish across individuals and species.